Peran Badan Kontak Majlis Taklim (BKMT) Kota Medan dalam Meningkatkan Pemahaman Keagamaan Masyakarat - Dalimunthe, Amsal Qori; Sinulingga, Neng Nurcahyati; Pohan, Intan Suryauliani; Sinaga, Elitimo; Lia, Agustina; Salsabila, Nurhaliza; Syahfitri, Syahfitri; Az-Zahra, Syauqi (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
This article aims to examine the role of the Badan Kontak Majelis Taklim (BKMT) of Medan City in enhancing the religious understanding of the community. The study uses a qualitative method with a descriptive approach, involving in-depth interviews and participatory observation with the management and members of BKMT in Medan City. The research findings indicate that BKMT serves as a center for religious development by designing various educational programs that guide the implementation of religious outreach in the community. Additionally, BKMT provides guidance and socialization to the management of BKMT at the sub-district level throughout Medan City and fosters close cooperation with its members and other partner organizations.